Nurses' involvement in the development and usability assessment of an innovative peripheral intravenous catheterisation pack: a mix-method study - Santos-Costa, Paulo (2022)
Guaranteeing peripheral venous access is one of the cornerstones of modern healthcare. Recent evidence shows that the lack of adequate clinical devices can result in the provision of substandard care to patients who require peripheral intravenous catheterization (PIVC). To address this challenge, we aimed to develop a PIVC pack for adult patients and assess the usability of this new device. Methods: Following a mix-method design, the PIVC pack development and usability assessment were performed in two phases with the involvement of its potential end-users (nurses). In phase one (concept and semi-functional prototype assessment), focus group rounds were conducted, and a usability assessment questionnaire was applied at each stage. In phase two (pre-clinical usability assessment), a two-arm crossover randomised controlled trial (PIVC pack versus traditional material) was conducted with nurses in a simulated setting. Final interviews were conducted to further explore the PIVC pack applicability in a real-life clinical setting. Results: High average usability scores were identified in each study phase. During the pre-clinical usability assessment, the PIVC pack significantly reduced procedural time (Z = −2.482, p = 0.013) and avoided omissions while preparing the required material (Z = −1.977, p = 0.048). The participating nurses emphasised the pack’s potential to standardise practices among professionals, improve adherence to infection control recommendations, and enhance stock management. Conclusions: The developed pack appears to be a promising device that can assist healthcare professionals in providing efficient and safe care to patients requiring a PIVC. Future studies in real clinical settings are warranted to test its cost-effectiveness.